2023
DOI: 10.37745/bjmas.2022.0107
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development Goals: Therapeutic Entrepreneurship and Mental Health Conditions

Abstract: This study analyzed therapeutic entrepreneurship and mental health condition in Nigeria. The study adopted quasi-experimental design and correlation design using systematic sampling and multi-stage cluster random sampling techniques. From the systematic population of 700 and sample size of 255 was determined using Slovin's formula at 0.05 level of significance, whereas 231 were deem fit after processing, retriever, coding and cleansing. The instrument was validated by experiential entrepreneurs and reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The concept of business creation is position on 'Lean Entrepreneurship. Business creation is centre on three key words;Value creation, Value capture and Wealth creation (Ovharhe, 2023). https://journals.e-palli.com/home/index.php/ajsde Am.…”
Section: Business Creationmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of business creation is position on 'Lean Entrepreneurship. Business creation is centre on three key words;Value creation, Value capture and Wealth creation (Ovharhe, 2023). https://journals.e-palli.com/home/index.php/ajsde Am.…”
Section: Business Creationmentioning
confidence: 99%
“…During patronage, it will be observed that the customer develop upward spiral of awe, joy and happiness that leads to an increase on return on investment (ROI), return on asset (ROA) and Return on Equity (ROE). Value creation is anchor on customer convenience, customer feedback, customer satisfaction and customer care (Ovharhe, 2023). Value creation is circles on creating value for your client/customers satisfaction.…”
Section: Value Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…The business world is surrounded with vital opportunities in the long-run and short-run. The problem entrepreneurs encountered is how to be optimistic about sustainability, survival and success of the new business, especially in the small and medium scales enterprises (SMEs) that spring up every second (Ovharhe, 2023). This means the concept of entrepreneurship entry that focus on identification of business opportunities and satisfaction of customer needs should be paramount issues and concerns to all entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%